RP-HPLC Estimation of Cefpodoxime Proxetil in Rat Plasma - Jeevana Jyothi, B.; Mounika, T. (Asian Journal of Chemistry, 2010)
A validated reverse phase HPLC method was developed for the estimation of cefpodoxime proxetil in rat plasma to determine pharmacokinetic parameters such as peak plasma concentration (Cmax), peak time (tmax), area under the curve (AUC0-24), absorption rate constant Ka and biological half-life (t½). The samples were chromatographed on a reverse phase column, Luna C18 (250 × 4.6 mm, 5 μm). Detection of cefpodoxime proxetil was carried out at 259 nm using SPDMP 10A photodiode array detector. Mixture of acetonitrile and phosphate buffer (pH 3) (70:30, v/v) was used as mobile phase. Aspirin was used internal standard. The drug was extracted from rat plasma samples by liquid-liquid extraction using methanol as extraction solvent. Calibration curve was linear over the range of 0.05-2 μg/mL of cefpodoxime proxetil. After oral administration of 1.4 mg/kg of rat weight of cefpodoxime proxetil, the plasma concentration-time curve was best confirmed to two-compartment open model. The maximum concentration (Cmax) 3.24 ± 0.037 μg/mL was obtained at time (tmax) of 2.0 ± 0.11 h. The mean area under the curve at 24 h, AUC0→24 was 39.77 ± 0.03 μg h/mL and at infinity time, AUC24→8 was 43.48 ± 0.06 μg h/mL. The biological half-life, t½ was 3.96 ± 0.034 h. The absorption rate constant, Ka was 0.135 ± 0.001 h-1 and the elimination rate constant, Ke was 0.175 ± 0.002 h-1.